Fabrication and characterization of 3D printing induced orthotropic functional ceramics. (4th November 2019) - Chavez, Luis A; Wilburn, Bethany R; Ibave, Paulina; Delfin, Luis C; Vargas, Sebastian; Diaz, Hector; Fulgentes, Christian; Renteria, Anabel; Regis, Jaime; Liu, Yingtao; Wicker, Ryan B; Lin, Yirong
Abstract: The orthotropic functional properties of additively manufactured ceramics due to the fabrication process was characterized in this study. Spherical, environmentally benign barium titanate (BaTiO3 ) powders were fabricated using binder jetting 3D printing. Dielectric and piezoelectric properties of these ceramics were characterized as a function of the printing orientation. The dielectric constant of the samples tested normal to the printing layers was observed to be 20% higher than those tested in the parallel fashion. Similarly, the piezoelectric response was found to be over 35% in the normal orientation. With these results, it was shown that the electroding orientation has a direct influence on the functional properties of additively manufactured ceramics. Overall, with less than 37% of the theoretical density, the average piezoelectric coefficient for the perpendicularly tested ceramics was found to be 152.7 pC N −1, which is 80% of the theoretical value. The high piezoelectric response obtained with such low densities can lead to the development of more mass efficient, and cost-effective sensing and energy harvesting devices, as well as structures that can be tuned to respond based on the direction of the loads applied.